Probabilistic design of a structure by the given level of reliability - Y. V. Krasnoshchekov; M. Yu. Zapoleva (Вестник СибАДИ)
The article substantiates the idea that currently there is sufficient data for probabilistic design of structures by the given level of reliability. The article is focused on the connection of reliability’s level with given probability of assurance factor. There is presented a comparison of assurance factors in different methods of calculation. The authors propose computational model of a stochastic assurance factor, distributed according to the normal law. There is given an example of calculating reinforced concrete roof plank on given reliability.